Orientalism, terrorism, Indigenism : South Asian readings in postcolonialism - Malreddy, Pavan Kumar, 1977- (SAGE, 2015)
Throws light over new conceptual approaches to Orientalism, terrorism, dalitbahujan movements and Post colonialism.